Peran Komitmen Organisasi dalam Memediasi Pengaruh Stres dan Kepuasan Kerja terhadap Turnover Intention Pada Karyawan Universitas X - Khaerani, Annisa’; Ardiansyah, Fuad; Kanisius, Thio (Jurnal Manajerial, 2026)
Background – The high turnover intention in college environments is a serious problem that might threaten the stability and continuity of an organization. People often want to leave this job because of high stress levels and low job satisfaction. Aim – The objective of this research is to analyze and identify the impact of job satisfaction and work-related stress on employee turnover intention, examining the role of organizational commitment as a mediator, while emphasizing the significance of job satisfaction as a dominant factor in reducing turnover intentions. Design / methodology / approach – This study employs a quantitative approach utilizing explanatory research design. The data collected via a questionnaire based on indicators of work stress, job satisfaction, organizational commitment, and turnover intention. SPSS is used to test validity and reliability. There were 140 respondents, all of whom were lecturers and educational staff at a university in eastern Indonesia, with data collection conducted both online and offline. SmartPLS software was used to analyze the data.. Findings – The findings of the study indicate that job satisfaction has a significant positive effect on organizational commitment and a significant negative effect on turnover intention. On the other hand, work stress does not have a significant effect on organizational commitment or turnover intention. Organizational commitment does not serve as a mediator in the relationship between work stress and job satisfaction with turnover intention. Conclusion – The empirical evidence suggests that job satisfaction is the most important factor in reducing turnover intention, while organizational commitment is more closely related to job satisfaction. Research implication – The outcomes of this study indicate that higher education institution management should concentrate on improving employee job satisfaction by strengthening a fair reward system, balancing work and life, and improving organizational communication. Limitations – This study is limited to a single educational institution in Eastern Indonesia, which may affect the generalizability of the findings. Moreover, the local organizational culture may affect how respondents viea HR policies. Further studies are recommended to include more institutions and employ a mixed methods approach.